THE CORRELATION BETWEEN GRAMMATICAL KNOWLEDGE AND WRITING ABILITY OF THE SECOND YEAR STUDENTS OF MAN 1 KUANTAN SINGINGI - Arianti, Yuanita; Azhar, Fadly; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aimed to find out whether there was a correlation between grammatical knowledge and writing ability of the second year students of MAN 1 Kuantan Singingi. The population was the second year students of MAN 1 Kuantan Singingi. The sample was decided by using cluster random sampling and there were XI MIA 2 and XI MIA 3 as the samples. Grammar test was applied to know the students’ grammatical knowledge and writing test was applied to know the students’ writing ability in analytical exposition text. The obtained data were analyzed by using Pearson Product Moment Formula which was assisted by IBM SPSS Statistics 23 program. From the analysis, it was found that the coefficient correlation was categorized as mediocre correlation. Therefore, the null hypothesis (Ho) is rejected and alternative hypothesis (H1) is accepted. In conclusion, there was a correlation between grammatical knowledge and writing ability of the second year students of MAN 1 Kuantan Singingi. The obtained determination coefficient (R Square) was twenty percent. This means that grammatical knowledge clarifies twenty percent towards writing ability. The rest eighty percents is probably due to other factors which are not involved in this research.Key Words: Correlation, Grammatical Knowledge, Writing Ability